THE EFFECTS OF LEAN AND SWEEP ON TRANSONIC FAN PERFORMANCE: A COMPUTATIONAL STUDY - JOHN D. DENTON (TASK Quarterly, 2002)
The aerodynamics of transonic fans is discussed with emphasis on the use of threedimensional design techniques, such as blade sweep and lean, to improve their performance. In order to study the interaction of these 3D features with the shock pattern a series of five different designs is produced and analysed by CFD. It is found that the 3D features have remarkably little effect on the shock pattern near the tip where the shock must remain perpendicular to the casing. Lower down the blade significant shock sweep, and hence reduced shock loss, can be induced by 3D design but this is usually at the expense of reduced stall margin and increased loss elsewhere along the blade span. Overall, very little change in efficiency is produced by blade sweep or lean. However, forwards lean of the rotor does produce a small increase in mass flow.